Analysis of Digital Media Framing in Aceh–North Sumatra News: Framing, Identity, and Power in the Representation of Regional Conflict - Ahmad Taufiq (Winaya Inspirasi Nusantara Foundation, 2025)
Background of the problem: Territorial disputes between subnational entities in Indonesia often occur without adequate public scrutiny, revealing gaps in understanding how such conflicts are symbolically constructed and mediated through digital media narratives. Purpose: This research investigates how media narratives shape power relations and construct regional conflicts discursively and ideologically through symbolic framing. Method: Using Pan and Kosicki’s framing analysis and Fairclough’s Critical Discourse Analysis (CDA) to examine 50 online news articles related to the island dispute between Aceh and North Sumatra. The study was conducted through text review, keyword frequency mapping, and actor-network visualization to explore the narrative structure and power relations in media discourse. Result: The research revealed that digital media coverage formed a centralized and hierarchical narrative by positioning state elites such as the President, Minister of Home Affairs, and national political figures as the leading actors in conflict resolution. Conflicts are framed in administrative and legalistic terms, thus obscuring the cultural-historical context and marginalizing the agency of local actors. This discourse pattern reproduces symbolic marginalization and reinforces power imbalances between the central and regional levels. Implication: The findings provide practical insights for media practitioners and policymakers to be aware of the ideological function of framing in conflict coverage and theoretical contributions to media and communication studies by showing how discourse structures reinforce state-centric narratives and marginalize subnational identities. The findings open space for further research on symbolic power in digital news.